1996
DOI: 10.1002/(sici)1098-240x(199612)19:6<499::aid-nur5>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and psychometric analysis of caregiver strain

Abstract: The purpose of the study was to establish the validity and reliability of an instrument for the measurement of caregiver strain, the Parent Caregiver Strain Questionnaire (PCSQ), with data from 283 adult children who were providing care to a neurologically impaired patient. Principal axis factor analysis of data rotated to an oblimin solution revealed five well-defined, first-order factors that explained 59% of the total variance in caregiver strain. The five-factors were interrelated with caregiver strain as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…The importance of caregiver and child quality of life is increasingly recognized as a critical outcome of any intervention in this population 12, 13. Previous studies of fundoplication in children with NI, GERD, and dysfunctional swallowing reported surgical mortality rates between 1% and 3% and other complications between 4% and 39%, reflecting the medical fragility of these children 5, 14–18.…”
mentioning
confidence: 99%
“…The importance of caregiver and child quality of life is increasingly recognized as a critical outcome of any intervention in this population 12, 13. Previous studies of fundoplication in children with NI, GERD, and dysfunctional swallowing reported surgical mortality rates between 1% and 3% and other complications between 4% and 39%, reflecting the medical fragility of these children 5, 14–18.…”
mentioning
confidence: 99%
“…12,13 Previous studies of fundoplication in children with NI, GERD, and dysfunctional swallowing reported surgical mortality rates between 1% and 3% and other complications between 4% and 39%, reflecting the medical fragility of these children. 5,14 -18 Some of these studies had longitudinal follow-up and reported long-term data.…”
mentioning
confidence: 99%
“…As defined by Brannan, Heflinger, and Bickman (1997), caregiver strain pertains to the "demands, responsibilities, difficulties, and negative psychic consequences of caring for relatives with special needs" (p. 212). England and Roberts (1996) suggest that caregiver strain encompasses three defining characteristics: "exhaustion," "emotional arousal," and "goal discrepancy distress" (p. 501). In congruence with this concept, caregiver strain additionally occurs in three dimensions: objective caregiver strain entailing the observable dimensions of burden; internalized strain referring to the internal subjective worrisome feelings of the caregiver; and externalized subjective caregiver strain regarding the negative feelings of the caregiver towards the recipient of care (Brannan et al, 1997).…”
Section: Theories Of Caregiver Stress and Strainmentioning
confidence: 99%